The Influence of School Administrative Staff Performance on Quality Non-Academic Administration Services - Rahmania, Dwi Anggia; Maisyaroh, Maisyaroh; Sunandar, Asep (Universitas Negeri Malang, 2024)
Schools as public institutions must be able to satisfy their customers. The paradigm of public service at the educational unit level should be changed from conventional conditions to conditions that are continuously updated so that when needed they are ready to provide services (on-service). School administrative staff must represent civil servants who are proactive, responsive and anticipatory towards the needs, aspirations and expectations of school stakeholders in accordance with Permendiknas Number 24 of 2008 concerning School Administrative Personnel Standards. Therefore, in addition to mastering various hard skills including technical skills, school administrative staff must also master various soft skills that are always displayed when providing services to create customer satisfaction.